Avaliação do desempenho da mini planta-piloto de flotação da CVRD: estudo comparativo com plantas industriais - Leticia Matte Loyola (2006)
In 1999, the Mineral Development Centre of CVRD (CDM) acquired a flotation device referred to as Mini Pilot Plant (MPP), which is able to run continuous flotation tests with drill core samples. Since then this equipment has been used to define the flotation circuit and process conditions during the feasibility phase of CVRDs copper sulphide projects. Santos et al. (2003) have validated the MPP as being a device able to reproduce industrial data. Nevertheless, this validation was done just on the rougher stage. The present work consists of a comparison and correlation of the results of all stages from a flotation MPPand industrial plants: Caraíba Mineração and Mineração Serra do Sossego, the first CVRDs copper mill. In order to make this comparison, both plants were completely sampled (grinding and flotation circuits) and the feed ore was tested on bench scale and on a MPP. The metallurgical and mass balances of each test were used for the comparison, inorder to evaluate the MPPs performance and conclude if it is possible to use it instead of conventional pilot plant.